A Study of Clinical Profile and Neutrophil-Lymphocyte Ratio in Clinical Outcome of Covid 19 Patients: Tertiary Care Centre in Bangalore - Ramalingaiah, Mamatha Tittamegalapalya; Jogihalli Mood, Jeetendra Kumar; Murthy, Vinutha Bagalur Srinivas; Singh, Virender (International Journal of Innovative Research in Medical Science, 2021)
Introduction: Corona virus disease is ongoing global pandemic, caused by severe acute respiratory distress syndrome corona virus 2 (SARS-Cov2). The virus was first identified in Wuhan, China in December 2019. The World Health Organization declared the virus a Public Health Emergency of International Concern on 30 January 2020, and later a pandemic on 11 March 2020.The severity of COVID-19 symptoms can range from asymptomatic milder forms to life-threatening. Severe illness is more likely in elderly patients and also in patients with co morbid conditions. Disease can transmit through air contaminated by droplets and small airborne particles. Aims: we aimed to know the clinical profile of covid 19 patients and also to co relate the neutrophil-lymphocyte ratio with clinical outcome of the disease. Materials and methods: This Prospective study was conducted in Patients admitted from August 2020 to October 2020. COVID-19 infection was diagnosed by RT-PCR and rapid antigen test (RAT) technique. Patients demographic data, clinical history was collected. Clinical assessment was performed. Laboratory investigations was sent. Patients were followed during the hospital stay. Appropriate statistical analysis was used Results: Males were commonly affected than females. Mean age of the patient was 61years. Diabetes was the most common co morbid condition. Fever was the most common symptom followed by cough, breathlessness. Neutrophil-lymphocyte ratio was elevated in intubated patients than in patients maintaining room air saturation, which was statistically significant (p value 0.001). Conclusion: Neutrophil-lymphocyte ratio (NLR) can be used as reliable, early marker for the disease progression of covid 19 disease.